THE INFLUENCE OF INQUIRY BASED LEARNING (IBL) TOWARD SCIENCE ‎LITERATION SKILL OF STUDENTS - Buchori Muslim; Zulfiani Zulfiani Zulfiani; Alif Luthvi Azizah (EDUSAINS, 2017)
This research aims to determine the effect of Inquiry-Based Learning (IBL) for students grade VIII’s scientific literacy skill based on the plant tissues concept. The method used in this research is a quasi-experimental method. The instrument used in this study is a science literacy test capabilities containing eight number of type Open-Constructed Response task which is follows the pattern of PISA’s framework and adapted the concept of plant tissues material. Observation sheet used to assess students in performing the learning stages of inquiry-based learning (IBL) particularly. The pretest and posttest in this experiment showed that there are  different result betwenscientifict literacy skill of students before and after the implementation learning model of inquiry-based learning (IBL). The scientifict literacy skill of students after the implementation  of IBL better than before the implementation. it is explained that the learning model of inquiry-based learning (IBL) affect the students’s scientific literacy skill apparently. Keywords: Inquiry-Based Learning (IBL), Plant Tissue, Scientifict Literacy Skill.